A Versatile Iridium(III) Metallacycle Catalyst for the Effective Hydrosilylation of Carbonyl and Carboxylic Acid Derivatives. Issue 32 (31st August 2017) - Corre, Yann; Rysak, Vincent; Trivelli, Xavier; Agbossou‐Niedercorn, Francine; Michon, Christophe
Abstract : A versatile iridium(III) metallacycle catalysed rapidly and selectively the reduction of a large array of challenging esters and carboxylic acids as well as various ketones and aldehydes. The reactions proceeded in high yields at room temperature by hydrosilylation followed by desilylation. Although the reactions of various aldehydes and ketones resulted exclusively in alcohols, the hydrosilylation of esters led to alcohols or ethers, depending on the type of substrate. Regarding the carboxylic acids, again the nature of the reagent controlled the outcome of the hydrosilylation reaction, either alcohols or aldehydes being formed. Abstract : A versatile Ir III metallacycle rapidly and selectively catalyses the reduction of various esters, carboxylic acids, ketones, and aldehydes. The reactions proceed in high yields at room temperature by hydrosilylation followed by desilylation. Depending on the substrate, esters are reduced to alcohols or ethers and carboxylic acids to alcohols or aldehydes.